Implementasi dan Pendampingan Sistem Informasi Presensi Berbasis Web di CV Patriot Kencana Medika - Rokhman, Arif Maulana; Fithri, Diana Laily (Al-DYAS, 2025)
This community service initiative was motivated by issues related to the manual attendance system at CV. Patriot Kencana Medika, which remains vulnerable to manipulation, inefficiency, and record-keeping errors—ultimately hindering effective human resource management. The program aimed to implement a web-based attendance information system integrating GPS location tracking and photo verification features to enhance transparency and efficiency in personnel administration. The approach used was participatory, involving training sessions, workshops, system development, and direct implementation within the company environment. Participants included administrators, human resource staff, and employees of CV. Patriot Kencana Medika. The results showed that participants were able to operate the system effectively following technical guidance and began to experience benefits such as improved data accuracy, ease of real-time attendance monitoring, and time efficiency in administrative reporting. Furthermore, the system's implementation successfully reduced potential attendance fraud and supported digital transformation efforts at the MSME level. The study concludes that training and implementing digital attendance systems can significantly improve human resource management quality and serve as a practical intervention model applicable to other MSMEs.